Marcadores SSR e STS ligados ao gene Co-4 que controla a reação à antracnose do feijoeiro comum - Mota, Ana Paula Simplício (2015)
The aim of this study was to validate molecular markers specifically associated with alleles of the Co-4 gene that controls the reaction to anthracnose of common bean, in particular the Co- 42 allele, and foment the integration of these markers in breeding programs aimed at developing resistant cultivars. For this, we evaluated 261 individuals F2 and 197 F2:3 progenies coming from crosses between SEL 1308 (carrier of Co-42 allele) and BRS Cometa. The studies confirm that the inheritance of reaction to anthracnose in SEL1308, using race 73 of Colletotrichum lindemuthianum, it is conditioned by an allele with complete dominance. In all, 15 markers were analyzed, ten STS (Sequence-Tagged Sites) and two SSR (Simple Sequence Repeat), recently identified by the Embrapa research group, and three SCAR (Sequence Characterized Amplified Regions) previously reported in the literature. Of these, 13 were polymorphic between the parents and segregated in the expected proportions to generations analyzed (3:1 or 1:2:1). Among the markers linked in repulsion phase, six STS (P8283-V1, P8284 -V1, P8285-V2, P8286-V1, P8286-V2 and P8286-V3) co-segregated at a distance of 2,64 cM from the allele Co-42 and 0,0 cM apart. As regards the SCAR markers, it was found that all are linked in coupling phase of the Co-42 allele at distances ranging from 2,93 cM (SAS13) at 6,42 cM (SH18). Of codominant markers, the STS P8286-V6 was mapped closest to Co-42 allele at a distance of 2,58 cM. Thus, the STS tested are excellent tools markers for assisted selection of genotypes resistant to anthracnose, since that present the highest selection efficiency estimates (84 - 99%) and the detection of plants carriers of different alleles of the Co-4 gene. However, only the SCAR SH18 possible the specific breakdown of Co- 42 allele, despite having less selection efficiency (85%) compared to the other analyzed markers. Therefore, it is recommend the combined or sequential use of P8286-V6 and SH18 markers for Co-42 selection at the expense of other alleles of the Co-4 gene. As for the selection of resistant genotypes in populations in which only the Co-42 allele is present, it is suggested to use only the P8286-V6 marker, which stands out for being codominant and strongly associated with the resistance allele. From a practical standpoint, the molecular markers validated in this study have shown great potential for use in the development of common bean cultivars resistant to anthracnose, being affordable to laboratories with different levels of infrastructure and highly efficient in monitoring genotypes carriers of resistance alleles of the loco Co-4.